Distribution of rare and endangered amphibians and reptiles in Primorsky Krai (Far East, Russia) - Irina V. Maslova; Ekaterina Yu. Portnyagina; Darja A. Sokolova; Polina A. Vorobieva; Mikhail V. Akulenko; Arseniy S. Portnyagin; Alexey A. Somov (Nature Conservation Research: Заповедная наука, 2018)
Information is given on new findings of five rare and endangered species of amphibians and reptiles inhabiting the Primorsky Krai: Onychodactylus fischeri, Pelodiscus maackii, Takydromus wolteri, Oocatochus rufodorsatus and Hebius vibakari. New locations are presented for the studied amphibians and reptiles. For the first time, Onychodactylus fischeri is reported here for the Partizanky Ridge, thus expanding its known habitat range in the south-western direction. Data on Takydromus wolteri, Oocatochus rufodorsatus and Hebius vibakari findings in western Primorsky Krai are provided for the first time. Habitat borders of Takydromus wolteri in the northern part of its distribution has been updated in various directions: to the west (Khankaysky District), north (Krasnoarmeysky District) and northeast (Olginsky District). The current model of habitat range and breeding places of Khankaysky population of Pelodiscus maackii has been demonstrated, taking into account submerging sandy spits on the western coast of Lake Khanka in 2014–2017. Rivers flowing into Khanka from the western site were shown to play an important role for inhabitance and reproduction of this species. Detailed information on distribution of Hebius vibakari in Primorsky Krai is given for the first time. This species is indicated to be common and sometimes numerous in the south and central parts of Primorsky Krai. The current state of this species' population was researched at locations indicated previously in the references. Some Protected Areas were analysed in the way they protect rare species of the Far Eastern herpetofauna. Hebius vibakari occurs consistently in the State Nature Reserve «Ussuriysky», State Nature Reserve «Kedrovaya Pad» and National Park «Land of the Leopard». Within their borders, the National Park «Bikin» and National Park «Udegeyskaya Legenda» are shown to have no effect on conserving populations of Pelodiscus maackii and Oocatochus rufodorsatus inhabiting basins of the River Bikin and River Bolshaya Ussurka. Their populations are distributed to the west of the national parks. Organising new Protected Areas is urgent for the Primorsky Krai in its western part (River Komissarovka basin) and in its south-eastern part (Livadiysky Ridge).